THE EFFECT OF LEARNING FACILITIES TOWARDS LEARNING MOTIVATION OF GRADE III STUDENTS AT SD NEGERI NOTOREJO, KECAMATAN GONDANG KABUPATEN TULUNGAGUNG - Eko Purnomo; Ria Fajrin Rizqy Ana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Abstract: Learning facilities refers to the facilities and infrastructures utilized to support the learning activities in order to achieve the goals of education. Motivation is a condition that encourages someone to do an activity so that he can achieve his goals. This research utilized a quantitative research method, namely ex post facto research. The data were analyzed by using prerequisite test and t test. The conclusion of the t test revealed that the score of tcount (3.681) > ttable (1.706) with a significance of 0.001≤0.05. Therefore, H0 was rejected and Ha was accepted. Thus, it can be concluded that learningfacilities affected the learning motivation of grade III students at SDN I Notorejo, Kecamatan Gondang, Kabupaten Tulungagung in the academic year 2018/2019. The results of this research were used as an effort to improve the quality of learning, especially in the availability of adequate learning facilities as a supporting factors to increase the students’ learning motivation.